Frequent Frauds Found in Governments and Not-For-Profits. - Dennis, Lynda (Aicpa Ser., 2018)
Recognizing fraudulent or deceptive practices is not always easy. What common frauds occur in governments and not-for-profits and how can they be avoided' Illustrating common frauds that make headlines and damage the reputations of government and not-for-profit entities, this title allows accountants to sharpen their forensic skills and uncover and avoid fraudulent activities. It provides an informative case study approach to real world situations. This title will show accountants how to do the following: -Determine how interim fraudulent reporting may affect planned reliance on internal controls and any related audit procedures.-Identify how personnel policies and procedures can be circumvented and lead to possible fraud or abuse.-Apply potential ways to follow up on noted indications of fraud, abuse, and weaknesses in internal control.-Determine how management override of internal controls can lead to possible fraud.-Analyze how bribes and kickbacks may occur.-Identify how donated assets and capital assets in general might be misappropriated.